Effects of Lonicera confusa and Astragali Radix extracts supplementation on egg production performance, egg quality, sensory evaluation, and antioxidative parameters of laying hens during the late laying period. (16th April 2019) - Xie, T; Bai, S P; Zhang, K Y; Ding, X M; Wang, J P; Zeng, Q F; Peng, H W; Lu, H Y; Bai, J; Xuan, Y; Su, Z W
ABSTRACT: Lonicera confusa (LC) and Astragali Radix (AR) extracts have been shown to have antioxidant and anti-inflammatory activities in human. To determine whether LC or/and AR extracts had similar functions to improve the egg production and egg quality, 1, 440 (52-wk-old) Lohmann pink-shell hens were randomly distributed into 4 treatments with nine replicates of 40 hens. The hens were fed a basal diet (CON) or the basal diet supplemented with 0.1% LC extracts, 0.1% AR extracts, or 0.1% LC extracts plus 0.1% AR extracts (LC-AR) for 12 wk. The eggs were collected on week 6 and 12 for analysis, and the plasma and ovaries were collected at end of trial. Dietary treatment did not influence ( P < 0.05) egg production, egg weight, and feed conversion ratio. However, LC-AR addition increased ( P < 0.02) yolk color and sensory quality of hard-boiled eggs compared to other groups. The LC-AR supplementation increased ( P = 0.02), and LC addition tended to increase ( P = 0.08) Haugh unit of eggs on week 12 compared to CON. The LC-AR supplementation decreased ( P < 0.001), and LC or AR individual addition tended to decrease ( P < 0.10) plasma malondialdehyde concentration compared to CON. Conversely, LC supplementation increased ( P = 0.02) total superoxide dismutase activity, and LC or/and AR supplementation increased the activities of manganese-containing superoxide dismutase (MnSOD) ( P < 0.08) and glutathione peroxidase (GSH-Px) ( P < 0.01) in plasma, and the mRNA abundance of MnSOD, GSH-Px1, and catalase in ovaries ( P < 0.05) compared to CON. The LC or/and AR supplementation decreased the concentrations of interleukin (IL)-6 and tumor necrosis factor alpha (TNF-α) in plasma ( P < 0.05), and the mRNA abundance of IL-6 and TNF-α in ovaries ( P < 0.04) compared to CON. These results suggested dietary inclusion of LC or/and AR improved the albumen quality, and a blend of LC and AR improved yolk color, which were associated with the enhancement of antioxidant capacity and the suppression of systemic inflammation in hens.